Quality Characteristics of Nutri-fried Noodles Made from Sweet Potato Tubers and Tops Ipomea batatas - de Jesus, Geraldine F.; Dicen, Shirley G.; Jarque, Maria Crisanta M. (JPAIR Multidisciplinary Research, 2016)
Noodles made from sweet potato can be a healthier alternative to commercially produced ones since it is rich in vitamins and minerals. The product has no artificial preservatives, and the sweetness of its taste comes naturally from the sugar content of the Camote tubers. The project is the second phase of a study on the development of nutri-noodles made from the tubers and tops of sweet potato. The study determined the physicochemical and microbial analysis and shelf-life of the product and verify its acceptability through quantitative testing. The sample was submitted to Department of Science and Technology Region V for analysis and the results were: 6.53% moisture, 0.13% free fatty acids and <150 CFU/g of yeast and mold count. Moreover, nutrition facts were also computed, Calories is 231, Total Fat= 4%, Cholesterol= 0%, Sodium= 4%, Total Carbohydrate= 6%, Dietary Fiber= 28%, Magnesium =13% and Vitamin B6= 12%. The shelf-life of the product is six months stored at room temperature. The Nutri-fried noodles were served with vegetable toppings, and as rated by the panelists the result was liked very much. After analyzing the quality characteristics of the product, it is recommended that the sample is ready for production and marketing.